2013
DOI: 10.1007/978-3-642-39715-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors in Enterprise Content Management: Toward a Framework for Readiness Assessment

Abstract: Enterprise content management (ECM) is an important enabler of information management, as it supports the creation, storage, retrieval, and retention processes of organizational documents and their content. The term ''ECM'' was coined in information management practice in the early 2000s, and it found its way into Information Systems (IS) research a few years later. While the level of research and publication activity in the field is increasing, we still see only a few academic reports on actual ECM practices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, it can be assumed that ECMS use and the users’ satisfaction with the ECMS not just influences the individual but at the same time the organization independent of the impact of the ECMS on the individual. While individual ECMS use might be beneficial for an organization in terms of a higher level of compliance or an increased level of efficiency, it might imply at the same time additional effort for a user’s daily routines by, for example, requiring the addition of metadata to information or scanning paper documents (Herbst, Simons, vom Brocke and Derungs, 2014) and as such not influencing a user’s impact positively. A summary of our hypothesis for the ECMS success model is given in Table II.…”
Section: Research Modelmentioning
confidence: 99%
“…However, it can be assumed that ECMS use and the users’ satisfaction with the ECMS not just influences the individual but at the same time the organization independent of the impact of the ECMS on the individual. While individual ECMS use might be beneficial for an organization in terms of a higher level of compliance or an increased level of efficiency, it might imply at the same time additional effort for a user’s daily routines by, for example, requiring the addition of metadata to information or scanning paper documents (Herbst, Simons, vom Brocke and Derungs, 2014) and as such not influencing a user’s impact positively. A summary of our hypothesis for the ECMS success model is given in Table II.…”
Section: Research Modelmentioning
confidence: 99%
“…Herbst et al [11] showed that ECM is an important enabler of informatioey identiied a set of critical success factors for ECM and develop a framework that helps organizations assess their readiness for ECM. In Herbst et al, this framework was developed following the data collected in workshops held between ECM project leaders and members of ive companies.…”
Section: Related Workmentioning
confidence: 99%